Model to estimate the project outcome´s likelihood based on social networks analysis - Abreu, António (2020)
One of the Key Challenges in the área of Project Management, is definitely, how to se up the best Project Team, regarding several key areasm such as: team experience, flexibility, engagement, know-how, and intra and cross-collaboration, so that Project Success Outcome can be achieved. Such best Project Team is definitely very difficult, if not extremely hard to define, especially when it comes to intra and cross-collaboration matters, where in projects environment, implies an extreme dynamic interaction between project people, throughout all the phases of a project lifecycle. Forecasting, to the possible extent, how that people dynamic´s interaction is a critical factor that can contribute to dictate how a project outcome will look like, is becoming a major concern for Risk Management, in Project Magagement. In this line of thought, the presente work aims to further contribute to this particular área of Risk Management, in Project Management, by exploring a new analysis approach, where it points out its focus towards project People, and how the dynamic interaction of project people, that delivers a project, acres its lifecycle, influences or not, a certain project outcome type (failure or success). To provide answer to this question, a heuristic model based on three scientific field pillars (Project Management, Risk Management, and Social Network Analysis Theory), is proposed in this work, which aims to identify a set of critical factors, regarding hoe people dynamically interact across the diferente phases of a project lifecycle, that are to be associated with project success, and project failure outcome.